2008
DOI: 10.1002/9780471729259.mc07b02s9
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Maintenance of Bdellovibrio

Abstract: Bdellovibrio bacteriovorus is a Gram‐negative bacterium that preys upon other Gram‐negative bacteria. It does this by penetrating the outer membrane and peptidoglycan to establish itself in the periplasm where it grows at the expense of the contents of the prey cell before ultimately lysing the prey. Wild‐type Bdellovibrio are prey‐(or host‐) dependent and the protocols described in this unit deal with the techniques required to grow this bacterium on its prey cells. Protocols are also presented to generate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 12 publications
0
53
0
Order By: Relevance
“…For the liquid cultures, cocultures (also termed prey lysates), and cultures for preparing PFU and single-colony growth on agar, we followed the following protocols based on methods from previous publications (1,2,9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the liquid cultures, cocultures (also termed prey lysates), and cultures for preparing PFU and single-colony growth on agar, we followed the following protocols based on methods from previous publications (1,2,9).…”
Section: Methodsmentioning
confidence: 99%
“…This process typically requires 3 to 4 h and takes place in a spherical bdelloplast, but under certain conditions, such as altered nutrient regimes (5) and downregulation of genes affecting motility (6), multiple bdelloplast morphologies and delayed bdelloplast lysis (5-8) have been documented. A review of much of the literature for B. bacteriovorus from its discovery in the early 1960s through 2008 will efficiently introduce the reader to this fascinating bacterium (3,9).…”
mentioning
confidence: 99%
“…5a) and motility were assayed for HI derivatives of the fliC1 merodiploid control, the motAB1 and motAB2 strains produced as described previously (17), and the original motAB3 HI strain. The axenic HI growth rate of each motAB mutant in PY medium was similar to that of the fliC1 merodiploid control, although each motAB deletion strain reached a higher final optical density.…”
Section: Resultsmentioning
confidence: 99%
“…All bacterial strains and plasmids used and created in this study are listed in Supplementary Table S1 (available with the online version of this paper). E. coli strains were grown in yeast extract and tryptone (YT) broth (Lambert & Sockett, 2008) at 29 uC with shaking at 200 r.p.m. for 16 h to give late-exponential-phase cultures for use as prey.…”
Section: Methodsmentioning
confidence: 99%
“…The plasmids were conjugated into B. bacteriovorus HD100 as described previously (Evans et al, 2007;Lambert et al, 2006;Lambert & Sockett, 2008). Subsequent HD and HI B. bacteriovorus strains were tested by culture and colony PCR for evidence of a secondary crossover event (Evans et al, 2007); putative deletion mutants were confirmed by Southern blotting (Southern, 1975) and sequencing (MWG Biotech) to confirm for Bd1802 the deletion of the gene and the loss of the suicide vector, and for tatA1 the insertion of the kanamycin cassette at the correct site, the lack of a wild-type gene and also for the loss of the suicide vector.…”
Section: Methodsmentioning
confidence: 99%